Gestão escolar no estado de São Paulo: perspectiva democrática ou modelo gerencial? uma análise a partir do relatório dos estudos do SARESP (2010 a 2012) - Oliveira, Tânia Cabral de [UNESP] (2014)
The school management has been the subject of discussion in political and academic by the centrality that has education in contemporary media. After the military regime as part of the process of democratization of society, democratic management education was established as guiding principle of education systems and schools by the Federal Constitution of 1988 and regulated by the Law of Guidelines and Bases of Education n ° 9.394/96, leaving the responsibility of Education Systems to establish the elements of achievement according to their peculiarities, since the community participated in drafting the proposal and the Pedagogical Councils were established to encourage participation. Because of changes in the political and economic environment, the democratic management of education was implemented taking into account the decisions of international bodies, losing their transformative potential of relations in society, and participation and autonomy, the main elements of achievement, became management techniques in management or co-management model. In São Paulo, the Basic Regimental Standards established the principle of democratic management and prepared the way for this mischaracterization occurred. Because of grammars that are steeped in Brazilian social practices, clientelism and patronage, bureaucracy that leads to authoritarianism and the nature of the liberal democratic state, the principle of democratic management encounters many obstacles to consolidate and lost their transformative potential. The present study aimed to determine whether, in the opinion of the school community, democratic management has consolidated your participation in school and in decision making in schools. We used data from the Study reports of SARESP the years 2010 to 2012, bringing together the answers of students, parents, teachers, principals and coordinators to questionnaires applied context before each issue of assessment for this,. These data are...